2020
DOI: 10.3928/01913913-20200504-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at Primary Intraocular Lens Implantation on Refractive Growth in Young Children

Abstract: Purpose: To evaluate the effect of age at primary intraocular lens (IOL) implantation on rate of refractive growth (RRG3) during childhood. Methods: A retrospective chart review was performed for children undergoing primary IOL implantation during cataract surgery. RRG3 was calculated for one eye from each patient using the first postoperative refraction, last refraction that remained stable (< 1.00 diopters [D] change/2 years), and the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Of these potentially relevant articles, 176 publications were excluded for various reasons, and 33 publications met the inclusion criteria and were included in this report. These comprised 3 RCTs [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 15 nonrandomized studies, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] relevant to research questions 1, 2, 3, and 4. No economic evaluations relevant to research questions 5 and 6 were identified. There were 16 clinical publications and 1 methods publication (which was not included in the overall count) 77 that reported on the same RCT -the Infant Aphakia Treatment Study (IATS).…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 4 more Smart Citations
“…Of these potentially relevant articles, 176 publications were excluded for various reasons, and 33 publications met the inclusion criteria and were included in this report. These comprised 3 RCTs [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 15 nonrandomized studies, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] relevant to research questions 1, 2, 3, and 4. No economic evaluations relevant to research questions 5 and 6 were identified. There were 16 clinical publications and 1 methods publication (which was not included in the overall count) 77 that reported on the same RCT -the Infant Aphakia Treatment Study (IATS).…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…The RCTs were conducted in the US [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]77 and India. 60,61 The nonrandomized studies were conducted in the US, [63][64][65] Germany, 66 Ireland, 67,68 UK, 69 Latvia, 70 China, 71 India, [72][73][74] France, 75 Brazil, 62 and Korea. 76 There were multiple publications for the IATS, which were published in 2020, 46,50,53 2016, 55,56 2015, 52,59 2014, 45,49,58 2013, 54,57 2012, 51 2011, 47,48 and 2010.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations